2018
DOI: 10.5194/hess-2018-518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of Evapotranspiration and Other Soil Water Budget Components in an Irrigated Agricultural Field of a Desert Oasis, Using Soil Moisture Measurements

Abstract: Abstract. An accurate assessment of soil water budget components (SWBCs) is necessary for improving irrigation strategies and optimizing the use of fertilizer in any water-limited environment such as the desert oases in arid northwestern China. However, quantitative information of SWBCs is usually challenging to obtain, because, since the water cycle is principally driven by irrigation (I), drainage (D), and evapotranspiration (ET) in desert oasis settings, none of the drivers can be easily measured under actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…The middle soil was leaching water to the soil below it but at the same time it was receiving water from the soil above it, which resulted in the slower rates of SWCs decrease at 70 and 100 cm depth than those at the top part (20 and 30 cm). The similar patterns of changes in SWCs were observed in irrigated agricultural field of a desert oasis in Northwest China (Li et al 2018).…”
Section: Discussionsupporting
confidence: 74%
“…The middle soil was leaching water to the soil below it but at the same time it was receiving water from the soil above it, which resulted in the slower rates of SWCs decrease at 70 and 100 cm depth than those at the top part (20 and 30 cm). The similar patterns of changes in SWCs were observed in irrigated agricultural field of a desert oasis in Northwest China (Li et al 2018).…”
Section: Discussionsupporting
confidence: 74%
“…The middle soil was leaching water to the soil below it but at the same time it was receiving water from the soil above it, which resulted in the slower rates of SWCs decrease at 70 and 100cm depth than those at the top part (20 and 30cm). The similar patterns of changes in SWCs were observed in irrigated agricultural field of a desert oasis in Northwest China (Li et al, 2018).…”
Section: Impact Of Infiltration From Precipitation or Flood Irrigation On Soil Watersupporting
confidence: 71%
“…The potential of microwaves in irrigation mapping is actually related to their sensitivity to SSM through the dielectric properties of the soil [17,18]. Several studies have also demonstrated the potential of microwave observations including SSM products for irrigation detection [11,[19][20][21]. Kumar et al [22] were the first to use SSM for irrigation mapping by exploiting the differences between coarse-resolution microwave SSM products (ASCAT, AMSR-E, SMOS, WindSat and ESA CCI) and SSM modeled by a land surface model that does not account for irrigation.…”
Section: Introductionmentioning
confidence: 99%